'UMRA DAN RUQBA: ANALISIS MENGENAI KESANNYA TERHADAP KONTRAK HIBAH DAN POTENSINYA SEBAGAI INSTRUMEN AGIHAN HARTA: 'Umra and Ruqba: An Analysis of Their Impact on The Hibah Contract and Their Potential as Instruments of Wealth Distribution - Nor Muhamad, Nasrul Hisyam (Jurnal Syariah, 2015)
Hibah (gift inter vivos) is one of the wealth distribution methods in Islamic law. It is considered as one of the most effective methods because the property owner is free to determine the beneficiary as well as the amount of property to be disposed. However, the issue that is still unresolved concerns the 'umra and ruqba stipulated in the hibah contract. Therefore, this article tries to analyse the position of the 'umra and ruqba according to the perspective of Islamic law. The writer also analyses the inclusion of 'umra and ruqba as conditions of hibah contract and their effect on the contract. The article focuses on the opinion of the Muslim scholars in the various schools about these issues and will then be revised based on the rules of Islamic law. Lastly, the situations where the 'umra and ruqba are relevant to be adapted as an instrument of the Islamic estate planning will be discussed. This discussion is limited to the theory of Islamic jurisprudence in respect of the two instruments, and therefore, its practice aspects in Malaysia are not specifically discussed.